La comunicación en el proceso de integración escuela familia de los estudiantes del octavo y noveno año de educación básica de la unidad educativa comunitaria intercultural bilingüe “TUPAK YUPANKI” del cantón Saraguro, comunidad Oñacapac, y la intervención del trabajador social - Cali González, Rosa Elizabeth (2019)
The present research work called COMMUNICATION IN THE PROCESS OF INTEGRATION SCHOOL FAMILY OF STUDENTS OF THE EIGHTH AND NINTH YEAR OF BASIC EDUCATION OF THE BILINGUAL INTERCULTURAL COMMUNITY EDUCATIONAL UNIT "TUPAK YUPANKI" OF SARAGURO CANTON, OÑACAPAC COMMUNITY, AND THE INTERVENTION OF THE SOCIAL WORKER , reveals the main findings obtained in field research, where the objectives that allowed theoretically substantiating the categories of analysis in relation to the object of study are met, such as identifying the causes and consequences that affect poor communication between parents and children within the family school integration process, to establish a social action plan whose purpose is framed in strengthening family communication. The results obtained in the research show that the main causes for poor communication are due to the intense working hours that parents keep, this does not allow them to maintain a fluid dialogue with the children, to this is added bad family relationships and emigration which results in the disinterest and demotivation of students by studying, thus generating low performance, loss of the year and school dropout. The methodology used was guided by the application of the scientific method, supported by auxiliary methods such as inductive, deductive, analytical and synthetic which allowed direct contact with students, parents and / or mothers and 5 teachers who became actors direct in this process, who allowed to clarify clearly that poor communication affects the process of school-family integration education. The techniques used were: the observation and survey that were applied to 34 students, 34 parents and / or mothers of family and 12 teachers; through instruments such as the observation form and the questionnaire based on multiple choice and criterion questions that allowed obtaining relevant information about the object of study. Finally, I consider it pertinent to present a proposal for social action that will help strengthen communication and family integration of the eighth and ninth years of basic education so that there is a true integration of the family school, which includes activities and strategies that enable a joint work of the educational trilogy. where parents are an active part of their children's education and not only delegate this activity only to teachers.